KEPALA MADRASAH SEBAGAI SUPERVISOR DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU PADA MIN MESJID RAYA BANDA ACEH. - Mardliah, Cut Zahri Harun, Sakdiah Ibrahim. (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstract: A principal as a supervisor has a role to stimulate, coordinate, and guide teachers to be able to improve their professional competence as a teacher and educator. The purpose of this study was to find out the programs, strategies, and obstacles faced by the principal in improving professional competence of teachers in Mesjid Raya Islamic State Elementary School of Banda Aceh. This study used descriptive method with qualitative approach. The techniques of data collection were observation, interview, and documentation. The subjects of this study were principal, teachers, and students. The results of this study showed that: (1) the supervision programs in improving professional competence of teachers were designed by the principal and were documented, which included annual and semester programs. It positively affected the improvement of professional competence of teachers that the learning activities became positive. The principal as a supervisor still carried out supervision activity, fostering, guidance, and directing teachers to improve professional competence in learning activities. (2) The implementation of principal’s supervision as a supervisor in improving professional competence of teachers included classroom counseling, classroom observation, and classroom visiting. These activities positively affected the teachers in improving their professional competence in term of preparing the lesson plans before teaching. (3) The obstacles faced in improving professional competence of teachers were the lack of time for the principal in determining the supervision schedule and the small number of teachers disagreed with the implementation of supervision, if it was for observing the learning process. In following up the result of supervision, the principal has used educative and persuasive approach like guiding teachers with difficulties through discussion, classroom visiting, and talks.Keywords: Principal, Supervisor, and Professionalism of Teacher.Abstrak: Kepala madrasah sebagai supervisor memiliki peran untuk menstimulir, mengkoordinasi dan membimbing guru-guru agar mampu meningkatkan kompetensi profesionalnya sebagai pengajar dan pendidik. Tujuan penelitian ini untuk mengetahui: program kepala madrasah, strategi, dan kendala dalam meningkatkan kompetensi profesional guru pada MIN Mesjid Raya Banda Aceh. Penelitian ini menggunakan metode deskriptif, pendekatan kualitatif. Teknik pengumpulan data dilakukan dengan observasi, wawancara, dan dokumentasi. Subjek penelitian adalah kepala madrasah, guru-guru, dan siswa. Hasil penelitian menunjukkan bahwa; 1) Program supervisi dalam meningkatkan kompetensi profesional guru disusun oleh kepala madrasah dan terdokumentasi, yang meliputi program kerja tahunan dan semesteran. Hal ini, berdampak positif terhadap peningkatan kompetensi profesional guru yaitu efektifnya kegiatan pembelajaran yang dilaksanakan. Kepala madrasah sebagai supervisor tetap melaksanakan kegiatan supervisi, mengadakan pembinaan, membimbing, dan mengarahkan guru untuk peningkatan kompetensi profesionalnya dalam kegiatan pembelajaran; (2) Pelaksanaan supervisi dalam meningkatkan kompetensi profesional guru, kegiatan yang dilaksanakan meliputi bimbingan kelas, observasi kelas, dan kunjungan kelas. Kegiatan ini berdampak positif bagi guru karena mampu meningkatkan kompetensi profesional mereka untuk senantiasa mempersiapkan perangkat pembelajaran sebelum mengajar; dan (3) Kendala yang ditemui dalam meningkatkan kompetensi profesional guru adalah keterbatasan waktu bagi kepala madrasah, untuk menentukan jadwal supervisi, masih ada sebagian kecil guru kurang mendukung kegiatan supervisi mengajar, bila disupervisi oleh kepala madrasah untuk melihat proses pembelajaran yang dilakukannya. Dalam menindaklanjuti hasil supervisi, kepala madrasah sudah melakukan pendekatan edukatif dan persuasif seperti pembinaan terhadap guru yang mengalami kesulitan melalui diskusi, kunjungan kelas, dan tanya jawab.Kata Kunci: Kepala Madrasah, Supervisor, dan Profesional Guru